2015
DOI: 10.1093/geronb/gbv032
|View full text |Cite
|
Sign up to set email alerts
|

Memory for Allergies and Health Foods: How Younger and Older Adults Strategically Remember Critical Health Information

Abstract: Objectives: While older adults often display memory deficits, with practice, they can sometimes selectively remember valuable information at the expense of less value information. We examined age-related differences and similarities in memory for health-related information under conditions where some information was critical to remember. Method: In Experiment 1, participants studied 3 lists of allergens, ranging in severity from 0 (not a health risk) to 10 (potentially fatal), with the instruction that it was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 38 publications
5
33
0
Order By: Relevance
“…Irrespective of study condition, participants showed an increase in selectivity across the lists of Segment 1. This is consistent with prior research demonstrating increases in selectivity with greater task familiarity (e.g., Castel, 2008; McGillivray & Castel, 2011; Middlebrooks et al, in press) and is indicative of strategy modification and/or more successful execution of an established value-based strategy. This selectivity continued to increase during Segment 2 in spite of mid-task shifts in study time; prior experiences with an alternate study rate did not appear to impact selectivity under novel conditions.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Irrespective of study condition, participants showed an increase in selectivity across the lists of Segment 1. This is consistent with prior research demonstrating increases in selectivity with greater task familiarity (e.g., Castel, 2008; McGillivray & Castel, 2011; Middlebrooks et al, in press) and is indicative of strategy modification and/or more successful execution of an established value-based strategy. This selectivity continued to increase during Segment 2 in spite of mid-task shifts in study time; prior experiences with an alternate study rate did not appear to impact selectivity under novel conditions.…”
Section: Discussionsupporting
confidence: 90%
“…So, in order to account for potential within- and between-subject differences in value-based recall strategies, hierarchical linear modeling (HLM) was used to analyze recall within each segment as a function of list and item value between the four study conditions (Middlebrooks et al, in press; Raudenbush & Bryk, 2002). HLM first clusters the data within each participant, thereby accounting for individual differences in strategy, and then considers potential differences in the impact of value and timing on recall across conditions, all while reflecting the to-be-remembered information as it was studied by participants and maintaining the overall data structure—a continuous value scale.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond motoric and self-referential processing, numerous other distinct factors can also be construed as being instances of motivated cognition. For instance, people have also been shown to be able to prioritize memory for words representing allergens and medication side-effects that were instructed to be more severe (Friedman et al, 2015;Middlebrooks et al, 2016), similar to prior prioritization studies that used reward values (Castel et al, 2002). It has also been shown in a number of studies that words processed with their survival relevance in-mind are remembered better than in the context of several other instructions (Kang et al, 2008;Nairne et al, , 2007Soderstrom & McCabe, 2011;Weinstein et al, 2008).…”
Section: Other Motivational Factorsmentioning
confidence: 87%
“…Providing more mechanistic similarities between emotion and reward, both have been shown to relate to autonomic function (e.g., pupil dilation and heart rate) (Abercrombie et al, 2008;Ariel & Castel, 2014;Bijleveld et al, 2009;Bradley et al, 2001Bradley et al, , 2008Buchanan et al, 2006;Fowles et al, 1982;Hochman & Yechiam, 2011;Manohar et al, 2017). Additionally, there are age-related differences in both emotion and reward processing, where older adults are more biased towards positively valenced and gain experiences, than negative/loss experiences (Barber et al, 2016;Carstensen & Mikels, 2005;Castel et al, 2016;Mikels & Reed, 2009;Mikels et al, 2016;Pachur et al, 2017;Samanez Larkin et al, 2007). This parallel may be somewhat exaggerated, however, as emotion and reward are sometimes experimentally operationalized similarly, and thus would produce similar effects in behavior.…”
mentioning
confidence: 99%